FORMATION OF BRAND IDENTITY OF THE MANUFACTURER OF YOGURT AND DESSERTS IN THE FVCG MARKET - Zhygalkevych, Zhanna M.; Kuznietsova, Kateryna V. (Journal of Strategic Economic Research, 2025)
The article examines the theoretical foundations of brand identity development for manufacturers operating in FMCG markets. Under conditions of intense competition and rapid changes in consumer markets, the formation of a strong brand identity becomes a key prerequisite for sustainable business development. The Ukrainian market of yogurt and dessert producers is no exception, as it is among the most sensitive to innovation, emotional perception, and consumer loyalty. The purpose of the article is to deepen theoretical and methodological approaches and to develop practical recommendations for brand identity development of manufacturers in the yogurt and dessert market. The research employs systematization and generalization to analyze approaches to brand identity formation and development; methods of analysis and synthesis to examine the marketing environment; and statistical methods to assess the effectiveness of market-driven initiatives. Results. The study reveals the essence of the brand and brand identity, the stages of brand identity formation, as well as the specific features of brand identity development in the fast-moving consumer goods (FMCG) market. In addition, a set of indicators for assessing brand identity strength is examined, incorporating both quantitative and qualitative metrics. Based on the research findings, a practical brand identity model and recommendations for its development are proposed, illustrated by the case of a dairy producer operating in the Ukrainian market. The conclusions emphasize that a brand ensures product identification and differentiation from competitors by creating unique perceptions that influence consumer choice, behavior, and loyalty. According to the works of David Aaker, the brand identity system comprises the product, the organization, the brand as a person, and the symbol associated with it. The specificity of building a brand identity system in the FMCG market lies in the need to create a holistic, visually recognizable, and emotionally clear brand system that can be quickly perceived by consumers, effectively scaled across the product portfolio, and perform efficiently under conditions of intense competition and frequent consumer–product interactions.